Femtosecond scanning, chopping (slicing) and measurement of length of electron bunches by laser pulses: principles of femtosecond oscilloscopes - Gazazian, E.D.; Guidi, V.; Ispirian, K.A.; Ispirian, M.K.; Kalantaryan, D.K. (Вопросы атомной науки и техники, 2007)
The equations of motion of electrons in a plane monochromatic wave with linear, circular and elliptical polarizations are solved taking into account the initial conditions. The cases when the interaction of the electrons with field of linearly and circularly polarized laser photon beams takes place during a finite time, while the electrons are detected after a long field-free region being scanned with period of the order of femtosecond, are suitable for femtoslicing and measurement of length of femtosecond electron pulses. The principles and limitations of slicing and of construction of laser femtosecond oscilloscopes are considered, and a scheme of experiment is proposed.